Use of Unmanned Aerial Vehicles for Traffic Surveys - Kampf Rudolf; Kubina Milan; Bartuška Ladislav; Soviar Jakub (Logi, 2022)
The paper deals with the topic of monitoring traffic using unmanned aerial vehicles. The main research goal was to test the possibility of using aerial vehicles for traffic engineering applications, especially for determining the traffic intensity on roads and for evaluating the data on traffic using video footage. The practical part of the paper focuses on the evaluation of data on traffic obtained by means of unmanned aerial vehicle at a selected intersection of roads. The data are evaluated using SW based on work with neural networks. A stationary system composed of an unmanned aircraft, camera system with a stabiliser, ground source with voltage converter, wire unwinding system and accessories were created by the staff of the ITB for the purpose of video recording the traffic from a 20-meter height. Such a tethered unmanned aerial system enabled a long-term operation in the air and a video recording lasting 1 hour at least.